Influence of inpatient opioid consumption on persistent use following total knee arthroplasty. Issue 2 (10th November 2020) - Pace, Meredith; Gannon, Kerri; Friedland, Matthew; Spurlin, Gervase; Price, Lori Lyn
Abstract : Background: Total knee arthroplasty (TKA) is associated with a high incidence of continued opioid use beyond the expected period of recovery. The aim of this study was to determine the influence of inpatient opioid consumption on the development of persistent use. Methods: Opioid-naïve patients undergoing primary, uncomplicated TKA were included in a prospective, observational study at a single institution. Postoperatively, opioids were prescribed by orthopedic advanced practitioners or resident physicians and administered by registered nurses. Individual inpatient prescriptions were adjusted, as needed, to facilitate optimal recovery conditions. Average hourly inpatient opioid consumption was calculated from total usage between midnight on the day of surgery until the time of hospital discharge. Persistent opioid use was defined as a prescription refill written by the orthopedic surgeon at the 6-week surgical follow-up visit. A multivariable regression model was used to identify independent risk factors associated with persistent use. Results: A total of 351 patients were included in the analysis. Persistent opioid use was identified in 17.4% (61) of patients overall. A history of alcohol abuse (OR 7.80; 95% CI 2.13 to 28.55, p=0.002) was identified as an independent risk factor. Inpatient opioid consumption in the top quartile (equivalent to more than 10 mg of oxycodone every 4 hours) was not found to be associated with persistent use. Conclusion: Larger amounts of opioid consumed in the hospital following uncomplicated, primary TKA may not be associated with an increased risk of persistent use at 6 weeks among opioid-naïve patients. Patients may have unique risk factors for prolonged opioid use that may not necessarily be apparent in the early postoperative period.